GENETIC VARIABILITY OF POLYMESODA EROSA POPULATION IN THE SEGARA ANAKAN CILACAP - Nuryanto, Agus; SUSANTO, AGUS HERY (BIOTROPIA, 2010)
<!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-US;} p.MsoBodyTextIndent, li.MsoBodyTextIndent, div.MsoBodyTextIndent {mso-style-unhide:no; mso-style-link:"Body Text Indent Char"; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:36.0pt; margin-bottom:.0001pt; text-align:justify; text-indent:-9.0pt; line-height:150%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-US;} span.BodyTextIndentChar {mso-style-name:"Body Text Indent Char"; mso-style-unhide:no; mso-style-locked:yes; mso-style-link:"Body Text Indent"; mso-ansi-font-size:12.0pt; mso-bidi-font-size:12.0pt; mso-ansi-language:EN-GB; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Abstract Mud clams Polymesoda erosa in the Segara Anakan Cilacap are highly exploited by the local communities for daily consumption. This is presumed causing population decline and potentially causing loss of genetic diversity. Genetic diversity level within population can be obtained by population genetic study using molecular marker such as randomly amplified polymorphic DNA (RAPD). Here we amplified RAPD marker using ten arbitrary primers to assess genetic diversity of P. erosa population in the Segara Anakan Cilacap to provide genetic data for its sustainable use. The result proved that the used RAPD marker has high polymorphisms. The mud clam population was also showed a high level of heterozigosity and genetic diversity.Â  This has important implication for the management plan towards ustainable use of P. erosa in the Segara Anakan Cilacap. Â  Key words: mud clam, RAPD, polymorphism, genetic diversity